Experimental implementation of low-cost and robust sensorless control based on SOGI-FLL estimator for electric vehicles - Riad Bouzidi; Ismail Ghadbane; Mohammed Boukhari; Ahmed Bendib; Abdelhammid Kherbachi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Sensorless control techniques of electric motor dedicated to electric vehicles (EVs) offer low-cost and high operating performance. In this paper, a low-cost and robust speed-sensorless control scheme based on a second-order generalized integrator-frequency-locked loop method (SOGI-FLL) is proposed with only one current sensor. The SOGI-FLL is introduced to estimate accurately the motor angular speed from a measured current signal. While the scalar control technique, based on a single loop speed regulation, is used to determine the ‎control signals. According to the proposed control scheme, the overall system will be very effective in terms of low-cost control and easy practical implementation, which have a great impact on electric vehicle applications. dSPACE micro labox platform is used to implement the proposed control scheme to drive an induction motor. The obtained results confirm the effectiveness and high performance of the proposed control to properly estimate the angular speed and drive the induction motor.